Composite electrolyte, preparation method thereof and battery

By forming the first modifier layer of the first modification layer of the silicon oxygen key connection on the solid -state electrolyte matrix, the second modifier layer of the covalent coupling connection is solved, and the problem of poor puzzle electrolyte to the water stability of water, and the higher air stability And lower interface impedance.

CN119361801APending Publication Date: 2025-01-24CHONGQING CHANGAN AUTOMOBILE CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411478923.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Garnet electrolyte has poor stability to water and is easy to react with water in the air, which limits its application range. At the same time, it is difficult to control the uniformity and thickness of the coating to achieve accurate accuracy.

Method used

A compound electrolyte is provided, including solid electrolyte matrix, first modifiers, and second modifiers. The first modifier layer is connected to the solid electrolyte matrix through the silicon oxygen bond. The second modification layer is connected to the first modified layer through the first co -price coupling group through the first co -price puppet group, forming a coverage layer to improve stability and reduce impedance.

Benefits of technology

It effectively improves the stability of the composite electrolyte in the air, reduces the interface impedance, and enhances the electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361801A_ABST
    Figure CN119361801A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical batteries, in particular to the technical field of battery electrolytes, and particularly relates to a composite electrolyte, a preparation method thereof and a battery. The composite electrolyte comprises a solid electrolyte matrix, a first modified layer and a second modified layer. And the first modified layer is connected with the solid electrolyte matrix through a silicon-oxygen bond. The second modified layer is connected with the first modified layer through a first covalent coupling group, and the second modified layer and the first modified layer coat the solid electrolyte matrix. Wherein the first covalent coupling group does not comprise a silicon-oxygen bond. The first modified layer is connected with the solid electrolyte matrix through the silicon-oxygen bond, so that the first modified layer covers the surface of the solid electrolyte matrix, erosion of water and / or carbon dioxide is prevented, and the stability of the composite electrolyte in air is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of chemical battery technology, in particular to the field of battery electrolyte technology, and specifically to a composite electrolyte and a preparation method thereof, and a battery. Background Art

[0002] Solid-state batteries have received extensive attention in recent years due to their advantages such as high safety, high energy density and long cycle life. The application of solid-state electrolytes aims to improve the safety and electrical performance of batteries. Garnet electrolyte, as a new type of solid-state electrolyte material, has become an important candidate material in the field of solid-state batteries due to its excellent lithium ion conductivity and good chemical stability.

[0003] However, garnet electrolytes have poor stability to water and are very easy to react with water in the air, which limits their application scope. In addition, it is difficult to achieve very precise control of the uniformity and thickness of the coating. Although related technologies have improved the stability of garnet electrolytes to water to a certain extent, they have also created new problems such as excessively high interface impedance.

[0004] Therefore, it is expected that a composite electrolyte, a preparation method thereof, and a battery can overcome the above problems. Summary of the invention

[0005] The present disclosure provides a composite electrolyte and a preparation method thereof, and a battery, which can improve the air stability of a solid electrolyte matrix. The technical solution of the present disclosure is as follows:

[0006] On the one hand, a composite electrolyte is provided, comprising: a solid electrolyte matrix, a first modified layer and a second modified layer. The first modified layer is connected to the solid electrolyte matrix through a silicon-oxygen bond. The second modified layer is connected to the first modified layer through a first covalent coupling group, and the second modified layer and the first modified layer cover the solid electrolyte matrix. Wherein, the first covalent coupling group does not include a silicon-oxygen bond.

[0007] The first modified layer is connected to the solid electrolyte matrix through a silicon-oxygen bond, so that the first modified layer covers the surface of the solid electrolyte matrix, avoiding direct contact between water, air, etc. and the solid electrolyte matrix, preventing corrosion by water and / or carbon dioxide, and effectively improving the stability of the composite electrolyte in the air. The second modified layer is connected to the first modified layer through a first covalent coupling group. Compared with physical mixing, the connection of the first covalent coupling group is conducive to reducing the impedance of the composite electrolyte.

[0008] In a feasible embodiment, the first covalent coupling group includes at least one of an amide group, an amino group, an epoxy group, a hydroxyl group, a carboxyl group, an isocyanate group, and a carbon-carbon double bond.

[0009] In a feasible embodiment, the second modified layer includes: a functional group, and the electronegativity of the functional group is greater than or equal to 3.

[0010] In a feasible embodiment, the functional group includes at least one of a fluorine group, a carbon-carbon double bond, a carboxyl group, a sulfonic acid group, an ester group, a haloformyl group, a carbamoyl group, a cyano group, an aldehyde group, a carbonyl group, a hydroxyl group, an amino group, an ether group and a phenyl group.

[0011] The second modified layer is connected to the first modified layer through the first covalent coupling group, so that the second modified layer and the first modified layer are coated on the surface of the solid electrolyte matrix. Specifically, the second modified layer is connected to the first modified layer through a grafting reaction, such as an amidation reaction or an addition reaction, so as to graft at least one of the above functional groups to improve the electrochemical window and other properties of the composite electrolyte.

[0012] In a feasible embodiment, the first modified layer includes a lipophilic group.

[0013] In a feasible embodiment, the lipophilic group includes at least one of an epoxy group, an aromatic group, an alkenyl group, an alkoxy group, a silane group and a fluoroalkyl group.

[0014] In a feasible embodiment, the solid electrolyte matrix, the first modified layer coated on the solid electrolyte matrix and the second modified layer form modified particles. The composite electrolyte also includes: a cross-linking layer, the cross-linking layer wraps a plurality of the modified particles, and the cross-linking layer is connected to the modified particles via a second covalent coupling group.

[0015] After the modified particles are polymerized with the cross-linking agent, a covalent bond is formed between the first modified layer and the polymer, and the electrolyte and the polymer are integrated at the molecular level, which can improve the compatibility with the polymer electrolyte and thus reduce the interface impedance.

[0016] In a feasible embodiment, the second covalent coupling group includes at least one of a carbon-sulfur bond, a carbon-fluorine bond, a carbon-oxygen bond, and an ethylphenyl group.

[0017] In a feasible embodiment, the cross-linked layer is polymerized from at least one of the following polymer monomers: divinylbenzene, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, bisphenol A diglycidyl ether, glycidyl ether, maleic anhydride, adipic anhydride, toluene diisocyanate, methyltrimethoxysilane, trimethylolpropane methacrylate triacrylate, bis(terephthalate)ethylene glycol dimethacrylate.

[0018] In a feasible embodiment, the solid electrolyte matrix is ​​selected from Li7La3Zr2O 12 , or Li7La3Zr2O 12A compound in which at least one of Li, La and Zr is replaced by X; wherein X is selected from Al 3+ 、 5+ , Ga 3+ , Nb 4+ , Y 3+ , Fe 3+ , W 6+ 、Te 6+ , Ba 2+ 、Ce 4+ 、Ti 4+ , B 3+ and Sb 5+ At least one of .

[0019] In a feasible embodiment, the particle size of the solid electrolyte matrix ranges from 100 nanometers to 100 micrometers.

[0020] In another aspect, a battery is provided, comprising the composite electrolyte as described above, a first pole piece and a second pole piece, wherein the first pole piece and the second pole piece are located on opposite sides of the composite electrolyte.

[0021] On the other hand, a method for preparing a composite electrolyte is provided, comprising: under alkaline conditions, a first modified layer coats a solid electrolyte matrix and is connected to the solid electrolyte matrix through a silicon-oxygen bond; a second modified layer is formed, the second modified layer and the first modified layer coat the solid electrolyte matrix, and the second modified layer and the first modified layer are connected through a first covalent coupling group; wherein the first covalent coupling group does not include a silicon-oxygen bond.

[0022] In a feasible embodiment, the solid electrolyte matrix and the first modified layer and the second modified layer coated on the solid electrolyte matrix are called modified particles. The preparation method of the composite electrolyte also includes: forming a cross-linked layer. Wherein, the forming of the cross-linked layer includes: mixing the modified particles with a cross-linking agent; adding an initiator; heating, and the modified particles and the cross-linking agent are connected through a second covalent group to obtain a cross-linked layer.

[0023] It can be understood that the beneficial effects that can be achieved by the preparation method of the composite electrolyte and the battery provided by the above embodiments of the present disclosure can refer to the beneficial effects of the composite electrolyte described above, which will not be repeated here.

[0024] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings herein are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the description are used to explain the principles of the present disclosure, and do not constitute improper limitations on the present disclosure.

[0026] Figure 1 The present invention is a flow chart of a method for preparing a composite electrolyte according to an embodiment of the present disclosure. DETAILED DESCRIPTION

[0027] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.

[0028] Unless the context requires otherwise, throughout the specification and claims, the term "including" is to be interpreted as an open, inclusive meaning, that is, "including, but not limited to". In the description of the specification, the terms "one embodiment", "some embodiments", "exemplary embodiments", "examples" or "some examples" and the like are intended to indicate that specific features, structures, materials or characteristics associated with the embodiment or example are included in at least one embodiment or example of the present disclosure. The schematic representations of the above terms do not necessarily refer to the same embodiment or example. In addition, the specific features, structures, materials or characteristics described may be included in any one or more embodiments or examples in any appropriate manner.

[0029] In the following, the terms "first" and "second" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the embodiments of the present disclosure, unless otherwise specified, "plurality" means two or more.

[0030] “At least one of A, B, and C” has the same meaning as “at least one of A, B, or C” and both include the following combinations of A, B, and C: A only, B only, C only, the combination of A and B, the combination of A and C, the combination of B and C, and the combination of A, B, and C.

[0031] “A and / or B” includes the following three combinations: A only, B only, and a combination of A and B.

[0032] According to some embodiments of the present disclosure, a composite electrolyte is provided, comprising a solid electrolyte matrix, a first modified layer and a second modified layer. The first modified layer is connected to the solid electrolyte collectively through a silicon-oxygen bond. The second modified layer is connected to the first modified layer through a first covalent coupling group. The first covalent coupling group does not include a silicon-oxygen bond.

[0033] Exemplarily, the solid electrolyte matrix is ​​an amorphous garnet electrolyte nanopowder formed by crushing a single crystal garnet electrolyte. The garnet electrolyte can undergo ion exchange with the solution to generate lithium inorganic substances and produce lithium vacancies. In some feasible embodiments, the solid electrolyte matrix is ​​selected from a single crystal lithium lanthanum zirconium oxide (chemical formula Li7La3Zr2O12, referred to as LLZO) electrolyte or a doped lithium lanthanum zirconium oxide (chemical formula LiLaZrXO12), a compound in which at least one of Li, La and Zr in the doped lithium lanthanum zirconium oxide, i.e., Li7La3Zr2O12, is replaced by X. Wherein, X is selected from at least one of trivalent aluminum ion Al3+, pentavalent tantalum ion Ta5+, trivalent gallium ion Ga3+, tetravalent niobium ion Nb4+, trivalent yttrium ion Y3+, trivalent iron ion Fe3+, hexavalent tungsten ion W6+, hexavalent tellurium ion Te6+, divalent barium ion Ba2+, tetravalent cerium ion Ce4+, tetravalent titanium ion Ti4+, trivalent boron ion B3+ and pentavalent antimony ion Sb5+. It should be understood that the solid electrolyte matrix is ​​selected from lithium lanthanum zirconium oxide in the present disclosure for description, which is not a limitation on the solid electrolyte matrix, and the solid electrolyte matrix can also be selected from other garnet electrolytes. In some feasible embodiments, the solid electrolyte matrix can also be selected from oxide electrolytes.

[0034] In some feasible embodiments, the particle size of the solid electrolyte matrix ranges from 100 nanometers to 100 micrometers. For example, the particle size of the solid electrolyte matrix can be 100 nanometers, 500 nanometers, 1000 nanometers, 10 micrometers, 50 micrometers or 100 micrometers.

[0035] The first modified layer is connected to the solid electrolyte matrix through a silicon-oxygen bond, so that the first modified layer covers the surface of the solid electrolyte matrix, avoiding direct contact between water, air, etc. and the solid electrolyte matrix, preventing corrosion by water and / or carbon dioxide, and effectively improving the stability of the solid electrolyte particles in the air.

[0036] The second modified layer is connected to the first modified layer through the first covalent coupling group, so that the second modified layer and the first modified layer are coated on the surface of the solid electrolyte matrix. The second modified layer can further improve the electrical properties of the composite electrolyte. For the introduction of the second modified layer, please refer to the subsequent content, which will not be described in detail here. The second modified layer is connected to the first modified layer through the first covalent coupling group. Compared with physical mixing, the connection of the first covalent coupling group is conducive to reducing the impedance of the composite electrolyte.

[0037] Exemplarily, the material forming the first modified layer can be selected from at least one of 3-aminopropyltriethoxysilane (APTES), 3-glycidyloxypropyltrimethoxysilane (GPTMS), methyltrimethoxysilane (MTMS), phenyltriethoxysilane (PTES), vinyltrimethoxysilane (VTMS), (3-mercaptopropyl)trimethoxysilane (MPTMS), (3-isocyanatopropyl)triethoxysilane (ICPTES), (3-methacryloxypropyl)trimethoxysilane (MPTMS), bis(trimethoxysilyl)ethane (BTMSE) and (3-chloropropyl)trimethoxysilane (CPTMS).

[0038] The core reaction of the silicon-oxygen bond is the formation of silanol (Si-OH). The material forming the first modified layer is dissolved in a mixed solution of ethanol and water. The material is hydrolyzed to generate silanol, and the generated silanols further form silicon-oxygen-silicon bonds through condensation reaction, and finally form a network structure. Silanol reacts with the hydroxyl groups on the surface of the solid electrolyte matrix to form silicon-oxygen bonds between the first modified layer and the solid electrolyte matrix, so that the first modified layer covers the surface of the solid electrolyte matrix, avoiding direct contact between the solid electrolyte matrix and water and air, effectively improving its stability in the air and preventing erosion by moisture and carbon dioxide.

[0039] In some feasible embodiments, the above process is carried out in an alkaline environment, after the material forming the first modified layer is dissolved in a mixed solution of ethanol and water, a pH regulator is added to adjust the pH value of the solution to 8-12, and lithium lanthanum zirconium oxide powder is added after a period of reaction, and the reaction is continued to separate to obtain lithium lanthanum zirconium oxide powder coated with the first modified layer. The pH regulator can be selected from any one of ammonia water, sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution or sodium bicarbonate solution.

[0040] The alkaline environment is more conducive to breaking the silicon-oxygen bond precursor Si-OR (where R is an organic group) of the material forming the first modified layer, promoting the hydrolysis reaction, thereby forming silanols more quickly and evenly, producing more silanol functional groups, and the generated silanol functional groups are also more likely to undergo condensation reactions between the surfaces of the solid electrolyte matrix. In addition, in an alkaline environment, the rate of the condensation reaction is relatively slower and the controllability is better, avoiding the condensation reaction rate being too fast, resulting in an uneven and rough film. Therefore, the alkaline environment can form a dense and smooth silicon-oxygen network, which is conducive to improving the coating effect of the first modified layer and enhancing the interface bonding.

[0041] In some feasible embodiments, the first modified layer further includes a lipophilic group.

[0042] Exemplarily, the lipophilic group may be at least one of an epoxy group, an aromatic group, an alkenyl group, an alkoxy group, a silane group, and a fluoroalkyl group.

[0043] The presence of lipophilic groups, such as epoxy groups, can increase the dispersibility and stability of the solid electrolyte matrix, thereby improving its dispersion and adhesion. Epoxy groups are polar and can form strong interactions with other polar molecules, thereby providing better adhesion properties.

[0044] In some feasible embodiments, the first covalent coupling group includes at least one of an amide group, an amino group, an epoxy group, a hydroxyl group, a carboxyl group, an isocyanate group, and a carbon-carbon double bond.

[0045] Exemplarily, the material forming the second modified layer includes any one of perfluorooctanoyl chloride, acryloyl chloride and ethyl cyanoacetate.The material forming the second modified layer may be selected from carboxylic acid, carboxylic acid converted into acid chloride and carboxylic acid converted into ester.

[0046] The first modified layer coating the solid electrolyte matrix also includes an amino group, which undergoes an amidation reaction with a carboxylic acid or a derivative thereof to generate an amide group, so that the second modified layer is connected to the first modified layer through the amide group so that the second modified layer and the first modified layer are coated on the surface of the solid electrolyte matrix.

[0047] In some feasible embodiments, the second modified layer includes functional groups, and the electronegativity of the functional groups is greater than or equal to 3.

[0048] For example, the electronegativity of the functional group may be 3, 4, 5 or 6, etc., which is not limited here.

[0049] By reasonably setting the value range of the electronegativity of the functional group, the functional group of the second modified layer has a strong electron-withdrawing ability, so that the molecules in the composite electrolyte have a stable electron distribution under a high voltage environment, thereby reducing the disturbance of the electric field to the molecules, improving the stability of the composite electrolyte, and making the composite electrolyte have a higher electrochemical window.

[0050] Exemplarily, the functional group includes at least one of a fluorine group, a carbon-carbon double bond, a carboxyl group, a sulfonic acid group, an ester group, a haloformyl group, a carbamoyl group, a cyano group, an aldehyde group, a carbonyl group, a hydroxyl group, an amino group, an ether group, and a phenyl group.

[0051] The first modified layer is connected to the second modified layer by an amidation reaction or an addition reaction, thereby grafting at least one of the above-mentioned functional groups to improve the electrochemical window and other properties of the composite electrolyte. For example, when the functional group is selected from a fluorine-containing group, because the electronegativity of the fluorine atom is high (about 3.98), the attraction to the electrons around the fluorine group is very strong, thereby improving the electrochemical window of the composite electrolyte. When the functional group is selected from a cyano group, because the cyano group has a high electron attraction, it is worth the high electronegativity of the nitrogen atom and can effectively attract electrons. The above characteristics help the molecule to stabilize the electron distribution under a high voltage environment and reduce the disturbance of the electric field to the molecule. At the same time, the triple bond in the cyano group provides a strong π-conjugation effect, which is conducive to the uniform distribution of electrons in the molecule and increases the stability of the molecule. It can prevent the decomposition and breakdown induced by the electric field under a high voltage environment, thereby improving the electrochemical window of the composite electrolyte.

[0052] In some feasible embodiments, the solid electrolyte matrix, the first modified layer and the second modified layer coated on the solid electrolyte matrix are called modified particles. The composite electrolyte also includes a cross-linking layer, the cross-linking layer wraps a plurality of modified particles, and the cross-linking layer and the modified particles are connected via a second covalent coupling group.

[0053] Exemplarily, the second covalent coupling group includes at least one of a carbon-sulfur bond, a carbon-fluorine bond, a carbon-oxygen bond, and an ethylphenyl group.

[0054] Exemplarily, the material forming the cross-linking layer can be selected from at least one of divinylbenzene, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, bisphenol A diglycidyl ether, glycidyl ether, maleic anhydride, adipic anhydride, toluene diisocyanate, methyltrimethoxysilane, trimethylolpropane methacrylate triacrylate and bis(terephthalate)ethylene glycol dimethacrylate.

[0055] Exemplarily, the modified particles are mixed with a crosslinking agent, an initiator is added to the mixture and dissolved in a solvent, and the modified particles and the crosslinking agent are polymerized by heating. Exemplarily, the initiator can be selected from any one of azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), di-tert-butyl peroxide (DTBP) and ammonium persulfate (APS).

[0056] After the modified particles are polymerized with the crosslinking agent, a second covalent coupling group, i.e., a covalent bond, is formed between the second modified layer and the polymer, and the covalent bond is selected from, for example, a silicon-oxygen covalent bond. The solid electrolyte matrix, the first modified layer, the second modified layer, and the crosslinking layer are integrated at the molecular level, thereby reducing the interface impedance. For example, when the functional group of the second modified layer is selected from a carbon-carbon double bond, the composite electrolyte has a lower interface impedance and a higher ionic conductivity due to the high degree of crosslinking and better compatibility of the carbon-carbon double bond with the crosslinking agent.

[0057] According to some embodiments of the present disclosure, a battery is provided, comprising a composite electrolyte, a first pole piece and a second pole piece, wherein the first pole piece and the second pole piece are located on opposite sides of the composite electrolyte. Exemplarily, the first pole piece may be a positive pole piece of the battery, and the second pole piece may be a negative pole piece of the battery.

[0058] The battery is, for example, selected from a secondary battery, which may also be called a rechargeable battery or storage battery, and is a battery that can restore its charge through a reverse electrochemical reaction for repeated use. In the present disclosure, the secondary battery may be referred to as a battery for short.

[0059] According to the different materials of the positive electrode, secondary batteries can be divided into lithium cobalt oxide batteries, lithium manganese oxide batteries and lithium iron phosphate batteries. According to different types, secondary batteries can be divided into battery cells, battery modules and battery packs.

[0060] like Figure 1 As shown, Figure 1 This is a flow chart of a method for preparing a composite electrolyte according to an embodiment of the present disclosure. The method for preparing a composite electrolyte includes steps S20 to S40.

[0061] In step S20, under alkaline conditions, the first modified layer covers the solid electrolyte matrix and is connected to the solid electrolyte matrix through silicon-oxygen bonds.

[0062] Exemplarily, the material forming the first modified layer, i.e., the first modified material, is dissolved in a solvent to form a precursor solution, a pH regulator is added to the solution to adjust the pH value of the precursor solution to alkaline, and the first modified material is stirred to react so that the first modified material is hydrolyzed to generate silanols, and condensation reaction occurs between the generated silanols. Thereafter, a solid electrolyte matrix is ​​added thereto, and the stirring reaction is continued so that the first modified material after hydrolysis and condensation reacts with the hydroxyl groups on the surface of the solid electrolyte matrix to form a covalent bond, and the first modified material is fully modified on the surface of the solid electrolyte matrix through silicon-oxygen bonds, thereby obtaining a solid electrolyte matrix coated with the first modified layer.

[0063] In step S30, a second modified layer is formed, the second modified layer and the first modified layer are coated on the surface of the solid electrolyte matrix, and the second modified layer and the first modified layer are connected through a first covalent coupling group. Wherein, the first covalent coupling group does not include a silicon-oxygen bond. Step S30 may include step S31 and step S32.

[0064] In step S31 , the material for forming the second modified layer, ie, the second modified material, is dissolved in a solvent, and a catalyst and / or an acid scavenger is added to the solution.

[0065] For example, the acid scavenger may be triethylamine, and the catalyst may be 4-dimethylaminopyridine.

[0066] Hydrochloric acid may be generated during the reaction of the second modified material with the solid electrolyte matrix coated with the first modified layer. Triethylamine can neutralize the hydrochloric acid to generate triethylamine hydrochloride, thereby avoiding adverse effects of hydrochloric acid on the reaction.

[0067] 4-Dimethylaminopyridine, as an alkaline catalyst, can activate the second modified material, for example, can activate acryloyl chloride having a carbon-carbon double bond, thereby increasing the reaction rate and making the carbon-carbon double bond more fully grafted as a functional group.

[0068] In step S32, the solid electrolyte matrix coated with the first modified layer is added to the mixed solution, so that the amino group of the first modified layer undergoes an amidation reaction with the second modified material, thereby grafting functional groups. Exemplarily, the second modified layer and the first modified layer are coated on the surface of the solid electrolyte matrix.

[0069] In step S40, the modified particles are mixed with a crosslinking agent, an initiator is added to the mixture and dissolved in a solvent, and the mixture is heated to react in an inert atmosphere, so that the modified particles and the crosslinking agent are connected through the second covalent coupling group to obtain a crosslinked layer, that is, a covalent bond is formed between the polymer formed by the modified particles and the crosslinking agent, and they are integrated at the molecular level.

[0070] In some feasible embodiments, step S10 is further included before step S20.

[0071] In step S10, the solid electrolyte matrix is ​​cleaned with ethanol and dried in a vacuum oven.

[0072] The following are examples of the composite electrolyte preparation method provided according to the above content, and comparative examples of the composite electrolyte preparation method provided according to the related art.

[0073] Comparative Example 1

[0074] In step S1, the surface of the lithium lanthanum zirconium oxide is cleaned and treated. For example, the lithium lanthanum zirconium oxide powder or sheet is cleaned with ethanol, placed in a vacuum oven, and dried at 60° C. for 12 hours.

[0075] In step S2, pressing and sintering are performed. For example, cold isostatic pressing (CIP) is used to press lithium lanthanum zirconium oxide powder or sheet, and 300 MPa is applied to press it into a dense disc, for example, a disc with a diameter of 12 mm and a thickness of 2 mm. The pressed disc is sintered at 1200° C. for 10 hours.

[0076] Comparative Example 2

[0077] In step S1, the surface of the lithium lanthanum zirconium oxide is cleaned and treated. For example, the lithium lanthanum zirconium oxide powder or sheet is cleaned with ethanol, placed in a vacuum oven, and dried at 60° C. for 12 hours.

[0078] In step S2, GPTMS is hydrolyzed and the lithium lanthanum zirconium oxide is surface modified.

[0079] Exemplarily, a precursor solution for hydrolyzing GPTMS is prepared, the solution comprising 80 ml of ethanol and 4 ml of water, and glacial acetic acid is added to adjust the pH of the precursor solution to 4.

[0080] 2 mL of GPTMS was added to the precursor solution and magnetically stirred at room temperature for 30 min.

[0081] 1 g of lithium lanthanum zirconium oxide powder was added to the precursor solution and magnetically stirred at 60° C. for 6 to 8 hours.

[0082] The obtained slurry was separated at room temperature at a centrifugal speed of 8000 r / min, and washed with anhydrous ethanol 2-3 times.

[0083] After drying in a vacuum oven at 60° C. for 12 hours, lithium lanthanum zirconium oxide powder coated with GPTMS was obtained.

[0084] In step S3, a composite electrolyte membrane is prepared.

[0085] Exemplarily, different weight ratios of lithium lanthanum zirconium oxide powders coated with GPTMS were weighed and added into an acetonitrile solution for ultrasonic dispersion for 30 minutes.

[0086] Lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and polyethylene oxide (PEO) were added and dissolved in a molar mass ratio of EO:Li+=16:1, and stirred with a magnetic stirrer for 12 hours at room temperature to obtain a uniform slurry, wherein EO is the ethoxy group (-CH2CH2O-) in polyethylene oxide.

[0087] The slurry was allowed to stand to expel bubbles, and the slurry was evenly coated on a polytetrafluoroethylene plate with a scraper using a coating machine, and dried in a vacuum drying oven at 60°C for 24 hours to remove the acetonitrile solvent, thereby obtaining a LLZTO@GPTMS-PEO composite electrolyte membrane with a thickness of 40 μm.

[0088] Example 1

[0089] In step S1, the surface of the lithium lanthanum zirconium oxide is cleaned and treated. For example, the lithium lanthanum zirconium oxide powder or sheet is cleaned with ethanol, placed in a vacuum oven, and dried at 60° C. for 12 hours.

[0090] In step S2, APTES is hydrolyzed and surface modified.

[0091] Exemplarily, a precursor solution for hydrolyzing APTES is prepared by adding a proper amount of aqueous ammonia to an ethanol aqueous solution having an ethanol volume fraction of 2% to 5% to adjust the pH to alkaline, for example, a pH of 9.

[0092] APTES was added to the precursor solution and magnetic stirring was performed at room temperature for 30 min.

[0093] Lithium lanthanum zirconium oxide powder is added to the precursor solution, and magnetic stirring is performed at room temperature for 2 hours to 4 hours to allow APTES to fully modify the surface of the lithium lanthanum zirconium oxide to obtain a slurry.

[0094] The slurry was separated at a centrifugal speed of 8000 r / min at room temperature, and washed with anhydrous ethanol 2 to 3 times.

[0095] After drying in a vacuum oven at 60 °C for 12 h, LLZO@APTES powder was obtained.

[0096] In step S2, the hydrolysis reaction of APTES is as follows:

[0097] (C2H5O)3Si-(CH2)3NH2+3H2O→(HO)3Si-(CH2)3NH2+3C2H5OH

[0098] Specifically, the reaction formula is as follows:

[0099]

[0100] It can be seen that APTES hydrolyzes to generate silanol. The generated silanol reacts with the hydroxyl group on the surface of lithium lanthanum zirconium oxide as follows:

[0101] (HO)3Si-(CH2)3NH2+LLZO-OH→LLZO-O-Si-(CH2)3NH2+H2O

[0102] For example, it should be understood that after the hydrolysis of APTES, a condensation reaction is formed between lithium, lanthanum, zirconium and oxygen to form a silicon-oxygen bond (Si—O), and finally a network structure is formed, as shown in the following formula:

[0103]

[0104] In some feasible embodiments, ammonia water is added in step S2 to adjust the solution to an alkaline environment. For example, any one of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution and sodium bicarbonate solution can be used to adjust the pH value; the pH value of the alkaline environment ranges from 8 to 12. For example, the pH value of the alkaline environment is 8, 8.5, 9, 9.5, 10, 10.5, 11, 11.5 or 12, etc., which is not limited here.

[0105] The alkaline environment is conducive to breaking the silicon-oxygen bond precursor (Si-OR, where R is an organic group) and promoting the hydrolysis reaction, so the efficiency of APTES hydrolysis to generate silanol is high, the time is short and more uniform. Moreover, under alkaline conditions, the condensation reaction rate between silanol and lithium lanthanum zirconium oxide is slower and more controllable, and a silicon-oxygen network with good thickness uniformity, compactness and high smoothness can be formed, thereby improving the coating effect of APTES. Silanol further reacts with the hydroxyl group on the surface of lanthanum zirconium oxide to form a covalent bond between the first modified layer and the lithium lanthanum zirconium oxide particles, so that the first modified layer is coated on the surface of the lithium lanthanum zirconium oxide particles, avoiding direct contact with water and air, preventing erosion by water and / or carbon dioxide, and significantly improving the stability of lithium lanthanum zirconium oxide in the air and its stability to water.

[0106] In step S3, a fluorine-containing group is grafted.

[0107] Exemplarily, an acetonitrile solution of perfluorooctanoyl chloride PFOS-CL is prepared with a concentration of 0.1 mol / L to 1 mol / L, and triethylamine is added to the solution as a catalyst.

[0108] APTES-modified lithium lanthanum zirconium oxide is added to the mixed solution and reacted at room temperature or 50°C for 4 to 12 hours, so that the amino groups on the APTES-modified lithium lanthanum zirconium oxide undergo amidation reaction with perfluorooctanoyl chloride to graft fluorine-containing groups. The amide group is, for example, the first covalent coupling group, as shown in the figure below.

[0109] After the reaction was completed, the mixture was washed with acetonitrile to remove unreacted reagents and / or reaction by-products, and then further washed with ethanol, and dried in a vacuum oven at 60° C. for 12 hours.

[0110] In a feasible embodiment, the reaction of grafting fluorine-containing groups onto LLZO@APTES is as follows:

[0111] LLZO-O-Si-(CH2)3NH2+CF3(CF2)7COCl→LLZO-O-Si-(CH2)3NH-CO-(CF2)7CF3+HCl

[0112]

[0113] In step S4, the LLZO@APTES grafted with fluorine-containing groups obtained in step S3 is polymerized with a crosslinking agent.

[0114] For example, the LLZO@APTES grafted with fluorine-containing groups is mixed with an epoxy crosslinking agent, and the epoxy crosslinking agent can be selected from glycidyl ether.

[0115] AIBN initiator is added to the mixture, dissolved in a solvent and stirred evenly, wherein the solvent may be selected from acetonitrile or tetrahydrofuran.

[0116] The mixed solution was transferred to a reaction vessel and heated to 75° C. under an inert atmosphere for 5 hours to ensure that the polymerization reaction was complete to obtain a composite electrolyte.

[0117] In a feasible embodiment, the carbon-oxygen double bond in the grafted group is broken and connected with the cross-linking agent to form a second covalent coupling group, and the modified particles also achieve molecular-level polymerization with the cross-linking agent.

[0118] Example 2

[0119] In step S1, the surface of the lithium lanthanum zirconium oxide is cleaned and treated. For example, the lithium lanthanum zirconium oxide powder or sheet is cleaned with ethanol, placed in a vacuum oven, and dried at 60° C. for 12 hours.

[0120] In step S2, APTES is hydrolyzed and surface modified.

[0121] Exemplarily, a precursor solution for hydrolyzing APTES is prepared by adding a proper amount of aqueous ammonia to an ethanol aqueous solution having an ethanol volume fraction of 2% to 5% to adjust the pH to alkaline, for example, a pH of 9.

[0122] APTES was added to the precursor solution and magnetic stirring was performed at room temperature for 30 min.

[0123] Lithium lanthanum zirconium oxide powder is added to the precursor solution, and magnetic stirring is performed at room temperature for 2 hours to 4 hours to allow APTES to fully modify the surface of the lithium lanthanum zirconium oxide to obtain a slurry.

[0124] The slurry was separated at a centrifugal speed of 8000 r / min at room temperature, and washed with anhydrous ethanol 2 to 3 times.

[0125] After drying in a vacuum oven at 60 °C for 12 h, LLZO@APTES powder was obtained.

[0126] In step S2, the hydrolysis reaction of APTES is as follows:

[0127] (C2H5O)3Si-(CH2)3NH2+3H2O→(HO)3Si-(CH2)3NH2+3C2H5OH

[0128] After APTES is hydrolyzed, the hydroxyl groups on the surface of lithium lanthanum zirconium oxide react as follows:

[0129] (HO)3Si-(CH2)3NH2+LLZO-OH→LLZO-O-Si-(CH2)3NH2+H2O

[0130] In step S3, carbon-carbon double bonds are grafted.

[0131] Illustratively, the APTES-coated lithium lanthanum zirconium oxide is dispersed in dichloromethane.

[0132] Add acryloyl chloride to the solution and continue the reaction at room temperature for 4 to 6 hours to ensure that acryloyl chloride reacts completely with the amino groups on APTES.

[0133] After the reaction was completed, the product was washed with dichloromethane to remove unreacted acryloyl chloride and reaction by-products, and further washed with ethanol, and finally dried in a vacuum oven at 60°C for 12 hours.

[0134] In some feasible embodiments, after the APTES-coated lithium lanthanum zirconium oxide is dispersed in dichloromethane, triethylamine is added to the solution as an acid scavenger to prevent the hydrochloric acid generated during the reaction from adversely affecting the reaction.

[0135] In some feasible embodiments, after the APTES-coated lithium lanthanum zirconium oxide is dispersed in dichloromethane, 4-dimethylaminopyridine is added to the solution. 4-dimethylaminopyridine as an alkaline catalyst can activate acryloyl chloride, increase the reaction rate, and make the carbon-carbon double bond grafting effect better.

[0136] In step S4, the LLZO@APTES grafted with carbon-carbon double bonds obtained in step S3 is polymerized with a crosslinking agent.

[0137] For example, LLZO@APTES grafted with carbon-carbon double bonds is mixed with a cross-linking agent, and the cross-linking agent can be selected from divinylbenzene.

[0138] AIBN initiator is added to the mixture, dissolved in a solvent and stirred evenly, wherein the solvent can be selected from acetonitrile or triethylamine.

[0139] The mixed solution was transferred to a reaction vessel and heated to 75° C. under an inert atmosphere for 5 hours to ensure that the polymerization reaction was complete to obtain a composite electrolyte.

[0140] In a feasible embodiment, the carbon-carbon double bond in the grafted group is broken and connected with the cross-linking agent to form a second covalent coupling group, and the modified particles also achieve molecular level polymerization with the cross-linking agent. It should be understood that after the carbon-carbon double bond of the grafted group is broken, it can also be connected with the carbon-carbon double bond of another grafted group to polymerize.

[0141] Example 3

[0142] In step S1, the surface of the lithium lanthanum zirconium oxide is cleaned and treated. For example, the lithium lanthanum zirconium oxide powder or sheet is cleaned with ethanol, placed in a vacuum oven, and dried at 60° C. for 12 hours.

[0143] In step S2, APTES is hydrolyzed and surface modified.

[0144] Exemplarily, a precursor solution for hydrolyzing APTES is prepared by adding a proper amount of aqueous ammonia to an ethanol aqueous solution having an ethanol volume fraction of 2% to 5% to adjust the pH to alkaline, for example, a pH value of 10.

[0145] APTES was added to the precursor solution and magnetic stirring was performed at room temperature for 30 min.

[0146] Lithium lanthanum zirconium oxide powder is added to the precursor solution, and magnetic stirring is performed at room temperature for 2 hours to 4 hours to allow APTES to fully modify the surface of the lithium lanthanum zirconium oxide to obtain a slurry.

[0147] The slurry was separated at a centrifugal speed of 8000 r / min at room temperature, and washed with anhydrous ethanol 2 to 3 times.

[0148] After drying in a vacuum oven at 60 °C for 12 h, LLZO@APTES powder was obtained.

[0149] In step S2, the hydrolysis reaction of APTES is as follows:

[0150] (C2H5O)3Si-(CH2)3NH2+3H2O→(HO)3Si-(CH2)3NH2+3C2H5OH

[0151] After APTES is hydrolyzed, the hydroxyl groups on the surface of lithium lanthanum zirconium oxide react as follows:

[0152] (HO)3Si-(CH2)3NH2+LLZO-OH→LLZO-O-Si-(CH2)3NH2+H2O

[0153] In step S3, a fluorine-containing group is grafted.

[0154] Exemplarily, an acetonitrile solution of perfluorooctanoyl chloride PFOS-CL is prepared with a concentration of 0.1 mol / L to 1 mol / L, and triethylamine is added to the solution as a catalyst.

[0155] APTES-modified lithium lanthanum zirconium oxide is added to the mixed solution and reacted at room temperature or 50°C for 4 to 12 hours, so that the amino group on the APTES-modified lithium lanthanum zirconium oxide undergoes an amidation reaction with perfluorooctanoyl chloride to graft a fluorine-containing group.

[0156] After the reaction was completed, the mixture was washed with acetonitrile to remove unreacted reagents and / or reaction by-products, and then further washed with ethanol, and dried in a vacuum oven at 60° C. for 12 hours.

[0157] In a feasible embodiment, the reaction of grafting fluorine-containing groups onto LLZO@APTES is as follows:

[0158] LLZO-O-Si-(CH2)3NH2+CF3(CF2)7COCl→LLZO-O-Si-(CH2)3NH-CO-(CF2)7CF3+HCl

[0159] In step S4, the LLZO@APTES grafted with fluorine-containing groups obtained in step S3 is polymerized with a crosslinking agent.

[0160] For example, the LLZO@APTES grafted with fluorine-containing groups is mixed with a cross-linking agent, and the cross-linking agent can be selected from divinylbenzene.

[0161] AIBN initiator is added to the mixture, dissolved in a solvent and stirred evenly, wherein the solvent can be selected from acetonitrile or triethylamine.

[0162] The mixed solution was transferred to a reaction vessel and heated to 75° C. under an inert atmosphere for 5 hours to ensure that the polymerization reaction was complete to obtain a composite electrolyte.

[0163] In a feasible embodiment, the carbon-oxygen double bond in the grafted group is broken and connected with the cross-linking agent to form a second covalent coupling group, and the modified particles also achieve molecular-level polymerization with the cross-linking agent.

[0164] Example 4

[0165] In step S1, the surface of the lithium lanthanum zirconium oxide is cleaned and treated. For example, the lithium lanthanum zirconium oxide powder or sheet is cleaned with ethanol, placed in a vacuum oven, and dried at 60° C. for 12 hours.

[0166] In step S2, GPTMS is hydrolyzed and surface modified.

[0167] For example, GPTMS is dissolved in ethanol to form a solution with a concentration of 2%-5% (volume fraction), deionized water and sodium hydroxide (NaOH) solution are added, and the solution is adjusted to an alkaline environment to promote the hydrolysis and condensation reaction of GPTMS. The pH value in the alkaline environment is, for example, 10.

[0168] The reaction was carried out at room temperature for 1 to 2 hours to partially hydrolyze the GPTMS, and the cleaned lithium lanthanum zirconium oxide was immersed in the solution and magnetically stirred at room temperature for 2 to 4 hours to allow the GPTMS to modify the surface of the lithium lanthanum zirconium oxide.

[0169] The lithium lanthanum zirconium oxide was washed with ethanol to remove unreacted GPTMS and dried in a vacuum oven at 60 °C for 12 h to obtain LLZO@GPTMS powder.

[0170] In step S2, the hydrolysis reaction of GPTMS is as follows:

[0171] (CH3O)3Si(CH2)3OCH2CH(OH)CH2O+3H2O→CH2OCH2CH(OH)CH2Si(OH)3+3CH3OH

[0172] The condensation reaction of silanol (Si-OH) is as follows:

[0173] 2CH2OCH2CH(OH)CH2Si(OH)3→

[0174] CH2OCH2CH(OH)CH2Si-O-Si(OH)2CH(OH)CH2OCH2+H2O

[0175] After hydrolysis and condensation reaction, GPTMS reacts with the surface hydroxyl groups of lithium lanthanum zirconium oxygen as follows:

[0176] 2CH2OCH2CH(OH)CH2Si(OH)3+LLZO-OH→LLZO-O-Si-(CH2)3OCH2CH(OH)CH2O+H2O

[0177] In step S3, cyano groups are grafted.

[0178] The GPTMS-coated lithium lanthanum zirconium oxide was dispersed in ethanol, and ethyl cyanoacetate was added to the solution.

[0179] TEA was added to the mixed solution as an alkaline catalyst for the reaction, and the reaction system was placed in a condensation reflux device and stirred at 50° C. for 6 hours.

[0180] After the reaction, the solution was filtered to collect the product, which was washed several times with a mixed solvent of dichloromethane and acetonitrile to remove unreacted ethyl cyanoacetate and reaction byproducts, further washed with ethanol, and dried in a vacuum oven at 60°C for 12 hours to obtain cyano-grafted GPTMS-coated lithium lanthanum zirconium oxide particles.

[0181] In a feasible embodiment, the reaction of grafting cyanide groups onto GPTMS-coated lithium lanthanum zirconium oxide particles is as follows:

[0182] LLZO-O-Si-(CH2)3OCH2CH(OH)CH2O+NC-CH2-COOEt→

[0183] LLZO-O-Si-(CH2)3OCH2CHCN+EtOH

[0184] In step S4, PEO is dissolved in dimethyl sulfoxide (DMSO) to prepare a 5 wt % DMSO solution. LiTFSI is added to the DMSO solution to adjust its concentration to 10 wt %, and stirred until it is completely dissolved.

[0185] LLZO@GPTMS-CN grafted with cyanide groups was added to the solution, the mass ratio of LLZO@GPTMS-CN to the solution was maintained at 1:5, and the mixed solution was repeatedly stirred.

[0186] Add the crosslinking agent to the mixed solution and continue to stir the mixed solution to ensure that the crosslinking agent is evenly distributed and reacts with PEO.

[0187] The mixed solution was poured into the mold and heated at 60°C for 4 hours to perform a cross-linking reaction.

[0188] After the reaction is completed, the mixture is dried in a vacuum oven at 60°C for 12 hours to remove the solvent and solidify the cross-linked network to obtain a composite electrolyte.

[0189] Example 5

[0190] In step S1, the surface of the lithium lanthanum zirconium oxide is cleaned and treated. For example, the lithium lanthanum zirconium oxide powder or sheet is cleaned with ethanol, placed in a vacuum oven, and dried at 60° C. for 12 hours.

[0191] In step S2, VTMS (vinyltrimethoxysilane, molecular formula CH2=CH-Si(OCH3)3) is hydrolyzed and surface modified.

[0192] Exemplarily, VTMS is dissolved in ethanol to prepare a 0.1 M solution, the solution is slowly stirred at room temperature and a 0.1 M sodium hydroxide solution is slowly added dropwise to adjust the pH of the solution to 8 to 9 to promote the hydrolysis reaction of VTMS.

[0193] The stirring was continued for 30 minutes to allow the VTMS to be completely hydrolyzed to generate silanol groups. The cleaned lithium lanthanum zirconium oxide was immersed in the solution and stirred for 4 hours to ensure that the VTMS hydrolysis product was coated on the surface of the lithium lanthanum zirconium oxide.

[0194] After the reaction was completed, the product was separated by centrifugation, washed with ethanol and deionized water, and dried to obtain VTMS-coated lithium lanthanum zirconium oxide.

[0195] In step S2, the hydrolysis reaction of VTMS is as follows:

[0196] CH2=CH-Si(OCH3)3+3H2O→CH2=CH-Si(OH)3+3CH3OH

[0197] The reaction formula is as follows:

[0198]

[0199] After hydrolysis, VTMS reacts with the surface hydroxyl groups of lithium lanthanum zirconium oxide as follows:

[0200] CH2=CH-Si(OH)3+LLZO-OH→CH2=CH-Si(OH)2O-LLZO+H2O

[0201] The reaction formula is as follows:

[0202]

[0203] In step S3, methyl mercaptopropanesulfonate (abbreviated as: MPSE) is grafted.

[0204] Disperse the VTMS-coated lithium lanthanum zirconium oxide in ethanol and stir evenly.

[0205] MPSE was added to the solution, heated to 50°C, and stirred for 6 hours to allow the thiol (-SH) in MPSE to react with the vinyl (-CH2=CH2) in VTMS to be grafted onto the surface of lithium lanthanum zirconium oxide.

[0206] After the reaction, the product was separated by centrifugation, washed with ethanol and deionized water, and dried at 50°C. The reaction was as follows:

[0207] CH2=CH-Si(OH)2O-LLZO+HS-(CH2)2-SO3CH3→

[0208] LLZO-O-Si(OH)2(CH2)2S-CH2CH2SO3CH3

[0209] The reaction formula is as follows:

[0210]

[0211] In step S4, the lithium lanthanum zirconium oxide grafted with MPSE is dispersed in ethanol, and a crosslinking agent divinylbenzene (DVB) is added to the solution and stirred for one hour. After the crosslinking is completed, the product is separated by centrifugation, washed and dried. Divinylbenzene reacts with MPSE to form a crosslinked structure. The reaction at least includes another ethylene of divinylbenzene and another MPSE molecule or other reactive vinyl residues crosslinking to form a network structure, and the reaction chemical formula is as follows:

[0212] LLZO-O-Si(OH)2CH2CH2SCH2CH2SO3CH3-CH2CH-C6H4CH=CH2+HS-CH2CH2SO3CH3→cross-linked network

[0213] The electrolytes / composite electrolytes obtained in Comparative Example 1, Comparative Example 2, and Examples 1 to 4 were subjected to performance tests to obtain the results shown in Table 1.

[0214] Table 1 Test results of ionic conductivity, impedance, electrochemical window, crystal structure and surface morphology

[0215]

[0216] Exemplary, the test method is as follows:

[0217] 1. Pressing and sintering: The electrolyte / composite electrolyte was pressed by cold isostatic pressing, and 300 MPa was applied to form a dense disc (12 mm in diameter and 2 mm in thickness). The pressed disc was sintered at 1200° C. for 10 hours.

[0218] 2. Measure the impedance spectrum: Silver is coated on both sides of the sintered disc and dried, and the measurement is performed using an electrochemical workstation. The sample is clamped between two stainless steels to form an electrochemical cell. Ensure good contact between the sample and the electrode. For example, a spring-loaded electrode can be used to ensure pressure and contact. Connect the electrode to the impedance analyzer and set the frequency range (1MHz to 0.1Hz) and the AC signal amplitude (10mV).

[0219] 3. Test the electrochemical window: Prepare a Li / LLZO / Au battery and measure it using an electrochemical workstation. Clamp the sample between two stainless steels to form an electrochemical cell. Ensure good contact between the sample and the electrode. For example, a spring-loaded electrode can be used to ensure pressure and contact. Connect the electrode to an impedance analyzer with a scan rate of 1mV / s and a scan range of 0V to 5V.

[0220] 4. Crystal structure test: Use X-ray diffraction (XRD), operating tube current: 10mA, tube voltage: 30kV, scanning range: 10°~80°, step size: 0.02°.

[0221] 5. Surface morphology test: Use a scanning electron microscope (SEM) to scan the sample with a narrowly focused high-energy electron beam. Through the interaction between the beam and the material, various physical information is stimulated. This information is collected, amplified and re-imaged to achieve the purpose of characterizing the microscopic morphology of the material and to observe the morphology and composition of its surface ultrastructure.

[0222] It can be seen from Table 1 that compared with Comparative Example 1, the impedance of the composite electrolytes of Examples 1 to 4 is reduced. This is because the lithium lanthanum zirconium oxide is connected to the first modified layer through a silicon-oxygen bond, the first modified layer is connected to the second modified layer through a first covalent coupling group, and the modified particles formed by the lithium lanthanum zirconium oxide and the first modified layer and the second modified layer are connected to the cross-linked layer through a second covalent coupling group to form a composite electrolyte covalently connected at the molecular level. Therefore, the interfacial impedance of the composite electrolyte is significantly reduced.

[0223] The electrochemical windows of Examples 1 and 3 are relatively high, both at 5 V. This is because both Examples 1 and 3 are grafted with fluorine-containing functional groups, and the fluorine atoms have high electronegativity and strong attraction to surrounding electrons. The high electronegativity makes the chemical bonds formed by the fluorine atoms very stable and not easily destroyed by the external electric field. In addition, the carbon-fluorine bond energy is relatively high, making the carbon-fluorine bond stable and difficult to break.

[0224] The ionic conductivity of Example 2 is relatively high, which is 0.5 mS / cm. This is because Example 2 grafted a functional group carbon-carbon double bond, and the degree of cross-linking between the carbon-carbon double bond and the cross-linking agent is higher, and the compatibility with the cross-linking layer is better.

[0225] The electrochemical window of Example 4 is the highest among Examples 1 to 4, at 5.2 V. This is because the cyano group has a high electron attraction, and the nitrogen atom has a high electronegativity, which can effectively attract electrons, which helps the molecule to be stably distributed under a high voltage environment, thereby reducing the disturbance of the electric field to the molecule. At the same time, the cyano group includes a triple bond, i.e., a carbon-nitrogen triple bond, which can provide a strong π-conjugation effect, making the distribution of electrons in the entire molecule more uniform. This conjugation effect also increases the stability of the molecule, and can prevent electric field-induced decomposition and breakdown under a high voltage environment.

[0226] The above are only specific embodiments of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any changes or substitutions within the technical scope disclosed in the present disclosure should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A composite electrolyte, characterized in that: include: Solid electrolyte matrix; A first modified layer connected to the solid electrolyte matrix via a silicon-oxygen bond; a second modified layer connected to the first modified layer via a first covalent coupling group; The second modified layer and the first modified layer cover the solid electrolyte matrix; Wherein, the first covalent coupling group does not include a silicon-oxygen bond.

2. The composite electrolyte according to claim 1, characterized in that The first covalent coupling group includes at least one of an amide group, an amino group, an epoxy group, a hydroxyl group, a carboxyl group, an isocyanate group and a carbon-carbon double bond.

3. The composite electrolyte according to claim 1, characterized in that The second modified layer includes: a functional group, and the electronegativity of the functional group is greater than or equal to 3.

4. The composite electrolyte according to claim 3, characterized in that The functional group includes at least one of a fluorine group, a carbon-carbon double bond, a carboxyl group, a sulfonic acid group, an ester group, a haloformyl group, a carbamoyl group, a cyano group, an aldehyde group, a carbonyl group, a hydroxyl group, an amino group, an ether group and a phenyl group.

5. The composite electrolyte according to claim 1, characterized in that The first modified layer includes at least one of a lipophilic group and an amino group.

6. The composite electrolyte according to claim 5, characterized in that The lipophilic group includes at least one of an epoxy group, an aromatic group, an alkenyl group, an alkoxy group, a silane group and a fluoroalkyl group.

7. The composite electrolyte according to any one of claims 1 to 6, characterized in that The solid electrolyte matrix, the first modified layer coated on the solid electrolyte matrix, and the second modified layer form modified particles; The composite electrolyte further includes: a cross-linking layer, wherein the cross-linking layer wraps the plurality of modified particles, and the cross-linking layer and the modified particles are connected via a second covalent coupling group.

8. The composite electrolyte according to claim 7, characterized in that The second covalent coupling group includes at least one of a carbon-sulfur bond, a carbon-fluorine bond, a carbon-oxygen bond and an ethylphenyl group.

9. The composite electrolyte according to claim 8, characterized in that The cross-linked layer is polymerized by at least one of the following polymer monomers: divinylbenzene, ethylene glycol dimethacrylate, trimethylolpropane triacrylate, bisphenol A diglycidyl ether, glycidyl ether, maleic anhydride, adipic anhydride, toluene diisocyanate, methyltrimethoxysilane, trimethylolpropane methacrylate triacrylate, and bis(terephthalate)ethylene glycol dimethacrylate.

10. The composite electrolyte according to claim 1, characterized in that The solid electrolyte matrix is ​​selected from Li7La3Zr2O 12 , or Li7La3Zr2O 12 The compound wherein at least one of Li, La and Zr is replaced by X; wherein X is selected from Al 3+ 、 5+ , Ga 3+ , Nb 4+ , Y 3+ , Fe 3+ , W 6+ 、Te 6+ , Ba 2+ 、Ce 4+ 、Ti 4+ , B 3+ and Sb 5+ At least one of .

11. The composite electrolyte according to claim 1, characterized in that The particle size of the solid electrolyte matrix ranges from 100 nanometers to 100 micrometers.

12. A battery, characterized in that: Comprising a composite electrolyte as described in any one of claims 1 to 11; The first pole piece and the second pole piece are located on opposite sides of the composite electrolyte.

13. A method for preparing a composite electrolyte, characterized in that: include: Under alkaline conditions, the first modified layer covers the solid electrolyte matrix and is connected to the solid electrolyte matrix through a silicon-oxygen bond; A second modified layer is formed, wherein the second modified layer and the first modified layer cover the solid electrolyte matrix, and the second modified layer and the first modified layer are connected via a first covalent coupling group; wherein the first covalent coupling group does not include a silicon-oxygen bond.

14. The method for preparing a composite electrolyte according to claim 13, characterized in that: The solid electrolyte matrix and the first modified layer and the second modified layer coated on the solid electrolyte matrix are called modified particles; The method for preparing the composite electrolyte further includes: forming a cross-linking layer; Wherein, the forming of the cross-linked layer comprises: mixing the modified particles with a cross-linking agent; adding an initiator; By heating, the modified particles are connected to the cross-linking agent via the second covalent coupling group to obtain a cross-linking layer.

Citation Information

Cited By

  • Solid electrolyte material, electrode, battery and preparation method

    CN121076226A

  • Solid-state electrolyte material, electrode, battery, and method of preparation

    CN121076226B